MANAJEMEN PENGEMBANGAN SUMBER DAYA GURU DALAM MENINGKATKAN PROFESIONALISME PENDIDIK PAUD: TEACHER RESOURCE DEVELOPMENT MANAGEMENT IN IMPROVING THE PROFESSIONALISM OF EARLY CHILDHOOD EDUCATORS - Nurhafizah, Nurhafizah; Azzahra, Resa Tifeni (Thufuli, 2024)
The goal of human resource management is to optimise organisational work processes. To ensure that all instructors are qualified in the speciality of early childhood education and build the quality of educational institutions, kindergarten teacher has to complete certification standards. Kindergarten teachers avoid doing that because early childhood is a golden period. But teachers in kindergarten don't do that. Teachers only serve as sources of knowledge for their students, but in order to assist them in finding solutions to learning and creativity, they must be able to recognise the uniqueness of each student. This study used a qualitative case study methodology. Techniques for gathering data are done through documentation, interviews, and observation. Data analysis includes gathering, reducing, presenting, and generating conclusions, according to the Miles and Huberman model. Data analysis methods used in this study include data collection, data reduction, data presentation, and conclusion drawing, all of which are part of the Miles and Huberman model. Through 1) professional training; 2) teacher collective activities like Gugus, IGTKI, KKG, and PGRI; 3) participation in scientific forums in the form of technical guidance, workshops, and seminars; and 4) support in the learning process, the research results argue that teacher development at Arafah Kindergarten, Nanggalo District, is carried out through coaching, counselling, mentoring, and providing motivation and empowerment.